Pengaruh Pengaplikasian Bleaching terhadap Hasil Pewarnaan Rambut - Raniyatul Hapizo; Tyas Asih Surya Mentari (YASIN, 2026)
The bleaching process on hair has the potential to cause damage, such as making the hair dry, brittle, rough, broken, and prone to hair loss, so the frequency of its application needs to be considered in hair coloring practice. This study aims to analyze the differences in the results of one-time and two-time bleaching on the level of dryness, hair elasticity, and color results among the people of Padang City. This study employed a quantitative approach with a quasi-experimental method. The population and sample of the study consisted of six samples that were given one-time and two-time bleaching treatments. Data were collected through observation and documentation using an assessment instrument based on indicators of dryness level, hair elasticity, and color results. The data were analyzed using the t-test and the coefficient of determination test (adjusted R²). The results showed that one-time bleaching application produced a score of 2.71 on the dryness level with the category of dry, a score of 2.42 on hair elasticity with the category of strong, and a score of 2.47 on color results with the category of colored. Meanwhile, two-time bleaching application produced a score of 3.61 on the dryness level with the category of very dry, a score of 3.63 on hair elasticity with the category of very weak, and a score of 3.51 on color results with the category of very colored. The results of the hypothesis test showed that there was a significant effect between one-time and two-time bleaching applications on the level of hair dryness. Thus, the frequency of bleaching application has implications for changes in hair condition, especially in the level of dryness, so these findings can serve as a consideration in hair coloring practice so that aesthetic results continue to take hair health into account.